PENDEKATAN ANALISIS REGRESI INDIVIDUAL UNTUK DATA LONGITUDINAL - Surianto Bataradewa (Jurnal Natural, 2008)
Classical Regression analysis are usually used in analysing longitude data or repeated measurement data (where response from each individual were measured in a period of time). Assumption of the analysis is no correlation among a couple measurement at same object. Whereas the repeated measurement data in same object research usually have correlation. Neglecting of correlation in regresion analysis will result in an uncertain conclusion.Regression individually analysis for longitudinal data attention the influence of individual effect and its interaction with time. So that with the reason, withdrawal of conclusion will be more be trusted its truth.The research objective is to compare regression individually analysis approach for longitudinal data with classical regression analysis. Data in this research is used simulation data.Result of research indicate that regression individually analysis to longitudinal data very success improve information about change of response from time to time